Legal Protection for Wives Against the Transfer of Marital Joint Property - Surbakti, Tiara Putri (Indonesian Journal of Law and Justice, 2026)
Marriage establishes legal consequences, particularly the creation of joint marital property jointly owned by husband and wife. In practice, however, unilateral transfers of such property often conducted by the husband to parents or third parties are frequently used as a strategy to circumvent equitable distribution following divorce, thereby undermining the wife’s legal rights. This study aims to examine the legal regulation of joint marital property in Indonesia and to analyze the forms of legal protection available to wives against bad-faith transfers. The research employs a normative legal method, utilizing statutory, conceptual, and case-based approaches to assess relevant legal frameworks and judicial interpretations. The findings reveal that joint marital property is regulated under Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law, and the Civil Code; however, these frameworks do not explicitly provide sanctions for unilateral transfers, resulting in a significant legal gap. Judicial practice, as reflected in Supreme Court Decision Number 454 K/Pdt/2018, demonstrates that transfers conducted in bad faith particularly those intended to harm the wife’s interests may be declared null and void. This indicates an evolving judicial effort to address the deficiency in statutory regulation. In conclusion, although existing legal provisions recognize joint marital property, stronger and more explicit regulatory mechanisms are necessary to ensure legal certainty and protect the rights of wives. Legal protection may be pursued through both preventive measures, such as clearer legal norms, and repressive measures through judicial remedies.